PREPARATION OF COLD CREAM AGAINST CLINICAL PATHOGEN USING CARALLUMA ADSCENDENS VAR. ATTENUATA - MADASAMY, SUNDAR; SUNDAN, SURESH; KRISHNASAMY, LINGAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A simple formulation of cold cream from methanolic extract Caralluma adscendens var. attenuata (MECA) and their antimicrobial activity was tested against various clinical pathogens, namely, Escherichia coli, methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus faecium, and Candida albicans. Methods: Methanol extract of these plant extract was prepared by the Soxhlet method. We analyzed phytochemical nature of theses plant, and subsequently, a cream was formulated cold-cream C. adscendens var. attenuata (FCA) different concentration such as FCA 50 mg, FCA 100 mg, and FCA 200 mg. In the present study, aimed to the antimicrobial activity of cold cream was measured by agar well diffusion method, and standard antibiotic Neosporin (market available) cream was used as positive control and dummy cold cream (without-MECA) were used as the negative control. Results: Phytochemical screening showed that the plant extracts were found a rich source of secondary metabolites. For more, the efficacy of cold cream from MECA extracts to against the clinical pathogen. Positive control Neosporin and 200 mg FCA cream was a highly significant difference in the zone of inhibition when compared to dummy cream. The 200 mg FCA was activity against Escherichia coli, methicillin-resistant Staphylococcus aureus, vancomycin-resistant E. faecium, and C. albicans highly significantly difference (p<0.05) compared FCA 50 mg and FAC 100 mg creams. Conclusion: The results from this study suggested that the cold cream form base of MECA crude had antimicrobial activity in the different clinical pathogen. They could be used as an alternative source to conventional antimicrobial agents for the treatment of pathological infection.